Do Single-cell Experiments Challenge the Concept of Cell Type? - Gross, Fridolin (Organisms. Journal of Biological Sciences, 2023)
Recent debates among biologists have highlighted problems with the traditional concept of cell type, which is considered vague and subjective. Single-cell technologies reveal the limitations of the current concept by exposing a high degree of heterogeneity in cell populations. At the same time, some biologists believe that these technologies provide the basis for a more objective and precise concept of cell type that is not dependent on prior theoretical assumptions. In this paper, I explore the impact that single-cell experiments and analyses will have on the concept of cell type. Drawing on the practices of biologists using these methods, but also on more principled arguments, I argue that the idea of a purely theory-free classification is unlikely to be realized. However, single-cell technology may affect the concept of cell type in more subtle ways.